Age-Adapted Wellbeing in a Consolation for Old Age: Re-Reading Ciceros Cato Maior De Senectute (44 bce) - Jedan, Christoph (NTT, 2021)
As part of NTT JTSRs series on Key Texts, the present article discusses Ciceros dialogue Cato Maior De Senectute (44 bce). Over the longue dur\u2019ee of western cultural history, the dialogue has been a key cultural reference. Even today, after the rise of modern gerontology, it is frequently cited. However, prevailing interpretations are hard-pressed to offer an even-handed and plausible view of the text. On the one hand, Cicero is presented uncritically as having anticipated all the latest results of todays gerontological research. On the other hand, he is ridiculed as spokesman for a male Roman elite, drawing an unrealistically positive picture of old age. In this article a fresh interpretation is proposed, to contextualize and mitigate such extreme readings. De Senectute is primarily a consolation for old age, which uses themes and stratagems of the consolatory genre. It offers a more realistic view of old age than current ideas of successful ageing and can contribute to a concept of age-adapted wellbeing.